EVALUATION OF IMPROVEMENT IN RENAL FUNCTION AFTER FIRST-LINE CHEMOTHERAPY IN MULTIPLE MYELOMA PATIENTS PRESENTING WITH RENAL IMPAIRMENT - Hamdani, Syed Abdul Mannan; Wahab, Abdul; Azhar, Musa; Iftikhar, Faiza; Ahsan, Bushra; Ahmad, Usman (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the effect of response to first-line chemotherapy on renal functions in multiple myeloma (MM) patients.Study Design: Cross-sectional study.Place and Duration of Study: Shaukat Khanum Memorial Cancer Hospital, Lahore, from Jan 2013 to Dec 2017.Methodology: Multiple myeloma patients with renal impairment (RI) at baseline were included. Data was collected from the hospital registry.The variables assessed pre and post first-line chemotherapywere age, gender, initial estimated glomerular filteration rate and serum creatinine levels. Progression-free survivaland overall survival (OS) was calculated for both groups of patients i.e those who had improvement in renal funtions and those who did not show improvement. Kaplan-Meier curves were drawn, and SPSS-20 was used for data analysis.Results: Mean age was 48 ± 7 years. Out of 139 myeloma patients, 35 (25.1%) had RI at baseline. Males were 23 (65.7%), while females were 12 (34.3%). Cyclophosphamide, thalidomide and deamethsone (CTD)were used in the majority 30 (85.7%) followed by boretzomib, thalidomide and dexamethasone (VTD) in 2 (5.7%) patients. Boretezomib and dexamethasone (BorDex), lenalidomide and dexamethasone (Len Dex), lenalidomde, cyclophosphamide and dexamethasone (LCD) were given to 1 (2.8%) patient each. Serum creatinine levels normalized in 19 (54.3%). Dialysis was required in 11 (31.4%) patients out of which 3 (8.6%) got dialysis-independent while 8 (22.9%) patients remained dialysis-dependent. The medianoverall survival in whomcreatinine levels normalized was 35 months while it was 15 months in those in whom it did not normalize.Conclusion: Prompt administration of chemotherapy regimens can lead to an improvement in renal function....................